Análise da técnica de escaneamento de fonte com possível identificador de onda P, para potencial utilização em monitoramento microssísmico - Assunção, Dário Guedes Miranda de (2016)
The research and development of techniques of stimulation of oil reservoirs, that are no longer economically viable due to the low relative permeability, through of hydraulic fracturing, leveraged world production rates in recent years. The monitoring microseismics events, generated in this production environment, can provide important information about the reservoir. The application of microseismic monitoring, related to the injection of fluids, is being increasingly recurrent in the oil industry due to the capacity of this information assist in the development of the reservoir, the placement decision of new injections of fluid, location of new perforations, among others. The development and improvement of methods in microseismic monitoring is an important alternative of search for help in the development of producing oil fields, due to lack of methods that have low cost and so makes possible its use in fields low production. Thus, we propose in this paper an analysis of the computational viability and efficient in the use of the technical SSA with possible P-wave identifier, for possible use in monitoring microseismic events in environments with hydraulic fracturing operations. The computational processing was divided into three phases, two with synthetic data tests and one with real data application of perforating shot (cannonade shot). In the first phase of synthetic tests were analyzed positioning errors and origin time errors of an event (with real position at x = 0, y = 0 and z = -1km) with 3 and 08 receptors (different geometry of the real data) for different data and input parameters, for example, data without noise, data with noise (2, 5, 10, 20, 30 and 40%), different windows RPA/LPA, different amounts receptors, etc. In the second phase synthetic test were analyzed the positioning errors of an event (with real position x = 0, y = 0 and z = -0,7km) with 3 and 12 receptors (geometry similar to the real data), for only a data with random noise of 40% and different windows of RPA/LPA. And in the phase of real data test (13 different events positioned at x = 0, y = 0 and Z = different depths) analyzes were made with respect the results for event each positioning and origin times found for each event, using only one RPA/LPA window.